Seasonal variability of future extreme precipitation and associated trends across the Contiguous U.S. - Dollan, Ishrat Jahan; Maggioni, Viviana; Johnston, Jeremy; Coelho, Gustavo de A.; Kinter, James L. (Frontiers in Climate, 2022)
Global climate models and long-term observational records point to the intensification of extreme precipitation due to global warming. Such intensification has direct implications for worsening floods and damage to life and property. This study investigates the projected trends (2015-2100) in precipitation climatology and daily extremes using Community Earth System Model Version 2 large ensemble (CESM2-LE) simulations at regional and seasonal scales. Specifically, future extreme precipitation is examined in National Climate Assessment (NCA) regions over the Contiguous United States using SSP3-7.0 (Shared Socioeconomic Pathway). Extreme precipitation is analyzed in terms of daily maximum precipitation and simple daily intensity index (SDII) using Mann-Kendall (5% significance level) and Theil-Sen (TS) regression. The most substantial increases occur in the highest precipitation values (95th) during summer and winter clustered in the Midwest and Northeast, respectively, according to long-term extreme trends evaluated in quantiles (i.e., 25th, 50th, 75th, and 95th). Seasonal climatology projections suggest wetting and drying patterns, with wetting in spring and winter in the eastern areas and drying during summer in the Midwest. Lower quantiles in the central U.S. are expected to remain unchanged, transitioning to wetting patterns in the fall due to heavier precipitation. Winter positive trends (at a 5% significance level) are most prevalent in the Northeast and Southeast, with an overall ensemble agreement on such trends. In spring, these trends are predominantly found in the Midwest. In the Northeast and Northern Great Plains, the intensity index shows a consistent wetting pattern in spring, winter, and summer, whereas a drying pattern is projected in the Midwest during summer. Normalized regional changes are a function of indices, quantiles, and seasons. Specifically, seasonal accumulations present larger changes (~30% and above) in summer and lower changes (less than ~20%) in winter in the Southern Great Plains and the Southwestern U.S. Examining projections of extreme precipitation change across distinct quantiles provides insights into the expected variability of regional precipitation regimes over the coming decades.